2019
DOI: 10.1155/2019/9320701
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Potential Dermal Progenitor Cell Markers in the Tumour and Stroma of Skin Adnexal Malignant and Benign Tumours

Abstract: Stem cells are multipotent cells that maintain the skin epidermis including skin appendages such as hair follicle, sebaceous glands, and sweat glands. There is evidence that reciprocal signalling between the epidermis and the dermis plays an important role in skin development, homeostasis, wound repair, and skin cancer. The origin of skin cancer that derive from skin appendages is still controversial, including basal cell carcinoma and even more of rare tumours such as sebaceous carcinomas and whether those tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Analysis of human tissues showed that expression of LRIG1 and LGR5 was present in most sebaceous carcinomas but decreased compared to benign sebaceous adenomas and expression of SOX9 was absent in sebaceous malignancies ( 84 ). Dermal progenitors, such as cellular retinoic acid-binding protein 1 (CRABP1), were expressed at the tumor-stroma interaction site within the core of sebaceous carcinomas and CRABP1 and nestin expression was lower in sebaceous carcinoma than in benign sebaceous adenomas ( 85 ).…”
Section: Developmental Biology Of the Sgmentioning
confidence: 99%
“…Analysis of human tissues showed that expression of LRIG1 and LGR5 was present in most sebaceous carcinomas but decreased compared to benign sebaceous adenomas and expression of SOX9 was absent in sebaceous malignancies ( 84 ). Dermal progenitors, such as cellular retinoic acid-binding protein 1 (CRABP1), were expressed at the tumor-stroma interaction site within the core of sebaceous carcinomas and CRABP1 and nestin expression was lower in sebaceous carcinoma than in benign sebaceous adenomas ( 85 ).…”
Section: Developmental Biology Of the Sgmentioning
confidence: 99%
“…The DNA image cytometry may be helpful in distinguishing between malignant and benign follicular tumors [30]. Several markers reported to label dermal progenitor cells are preserved in the MANs, including the tumor stroma (CRABP1, Nestin, and Ephrin B2) [31]. Some authors recommend magnetic resonance imaging and fluorodeoxyglucose-positron emission tomography/ computed tomography to establish the extent of disease [32].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Basal cell and squamous cell carcinomas exhibit the enormous identified prevalence of malignant tumors [ 217 , 218 , 219 , 220 ]. These types of cancers are primarily developed from the hair follicle stem cells [ 218 , 221 ]. However, their growth and proliferation depend on initial burst neovascularization [ 222 , 223 ], in which obligatory entities are VEGF (vascular endothelial growth factor) [ 217 , 224 ] and EGFR (epidermal growth factor receptor) [ 218 , 222 ].…”
Section: Autoimmune Disorders and Cannabinoidsmentioning
confidence: 99%